Church planting in patronage cultures : aid dependency issues and missional implications from Korea to Cambodia - Oh, Robert (Regnum mini book series., 2020)
"Patronage governs most relationships in Global South cultures. However, regrettably, missionaries rarely recognise this prominent cultural reality. Moreover, misunderstanding patronage creates problems not only for missionaries but also for national pastors. This book shows that when a patron plays a role as a father, he plays a significant role in developing national pastors as church planters and offers an alternative reading of aid dependency as a relational concept rather than an economic one."--Publisher